Diversification patterns and size evolution in caviomorph rodents - Alvarez, Alicia (2017)
Caviomorph rodents are one of the most diverse mammalian groups in the Neotropics; they display astonishing eco-morphological variation, including unparalleled size range. Here we analyse evolutionary patterns among extant caviomorphs, particularly their rates of diversification and size evolution. The results show large heterogeneity in the evolutionary dynamics of caviomorphs. Three clear episodes of rapid increase of the diversification rate were detected; two of them during the Oligocene were related to the diversification of major clades; a third one, in the late Miocene, was related to the diversification of the genus Ctenomys. Regarding size, relatively low rates characterized much of Octodontoidea, the most speciose among the main caviomorph clades. Other clades, especially Cavioidea and Chinchilloidea, showed much accelerated evolutionary rates and the highest number of size changes, particularly increases; furthermore, they include extinct representatives that reached very large to gigantic size. Thus, although the macroevolutionary dynamics of caviomorphs were complex and heterogeneous in our study, the pathways followed by different clades seem to display their own particular characteristics. This should be analysed in greater depth through new, greater scale analyses incorporating the rich fossil record of caviomorphs, which contributes essential information to understand the evolution of these peculiar rodents.